2021
DOI: 10.1021/acs.joc.1c01369
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of Aryl Selenonic Acids and Some Unexpected Byproducts

Abstract: The synthesis of aryl selenonic acids was achieved from diverse aryl bromides via a one-pot method involving metalation, selenation, and oxidation with hydrogen peroxide followed by ion exchange to afford the pure products in 77−90% yield. An o-hydroxymethyl derivative was found to dehydrate readily, affording the first example of a cyclic selenonic ester, while two minor byproducts were isolated and shown by X-ray crystallography to be mixed salts of aryl selenonic acids with either the corresponding aryl sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…This correlates closely with the downfield signal at 1162.5 ppm in the precipitate. In our previous work [93], all of the selenonic acids studied produced 77 Se NMR signals in the 1020-1031 ppm range in D 2 O, consistent with the more upfield signal at 1020.2 ppm. These results suggest that the species present are the free seleninic and selenonic acids 3 and 14, respectively, and not the expected salt 16.…”
Section: Oxidation Of Ebselensupporting
confidence: 76%
See 2 more Smart Citations
“…This correlates closely with the downfield signal at 1162.5 ppm in the precipitate. In our previous work [93], all of the selenonic acids studied produced 77 Se NMR signals in the 1020-1031 ppm range in D 2 O, consistent with the more upfield signal at 1020.2 ppm. These results suggest that the species present are the free seleninic and selenonic acids 3 and 14, respectively, and not the expected salt 16.…”
Section: Oxidation Of Ebselensupporting
confidence: 76%
“…The selenonic acid derivative of selenocysteine has also been prepared and its x-ray crystal structure was determined [92]. More recently, we described an effective one-pot synthesis of various selenonic acids from aryl bromides [93]. On the other hand, the formation of the isomeric peroxyseleninic acid 15 from 3 does Scheme 3.…”
Section: Oxidation Of Ebselenmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2021, Sands et al reported the one-pot synthesis of structurally diverse selenonic acids in good yields (up to 90%) from elemental Se and aryl bromides. The reaction involves metalation using t -Butyllithium, selenation, and oxidation using H 2 O 2, followed by ion exchange using Rexyn 101( H ) ion-exchange resin ( Scheme 32 ) [ 81 ].…”
Section: The One-pot Multicomponent Combinatorial Synthesis Of Ose Co...mentioning
confidence: 99%
“…Here, the quinoline ligand not only facilitated the installation of Se in the benzamide ring but also avoided the use of 1,10-phenanthroline ligand in catalysis as itself serves as a ligand and also helps in stabilizing high oxidation VI state of selenium. In comparison to divalent and tetravalent, hexavalent organoseleniums are underexplored and mainly used as peroxide-decomposing/activating mimetics. , …”
mentioning
confidence: 99%